Relationship Between Employee Satisfaction and Perceived Organization Support on Individul Performance: Job Involvement As a Mediating Variable at Sharia Commercial Bank In Makassar City - Musafir, Musafir (Green Publisher Indonesia, 2022)
The level of employee confidence in organizational support will be influenced by the evaluation of their experiences and observations about the way the organization treats its employees in general. This research and to analyze the effects of the satisfaction and perception of the employees on the organizational support on the job involvement and the performance of the employees. The research population comprised all the 463 employees in six Syariah Public Banks in Makassar City, and the total of 203 samples of each bank. The data collection was done by using questionnaires and then analyzed using the analysis of the Structural Equation Model (SEM) through the software of Amos version 22. The research results indicated that (1) the satisfaction of the employees had a positive and significant effect of the job involvement and the performance of the employees; (2) that the perception organizational support had an insignificant effect on the job involvement and performance of the employees; and (3) the Job involvement each had a positive and significant effect on the performance of the employees.